213 PROMOTING HELMET USE DURING HORSEBACK RIDING IN BUFFALO, WYOMING. Issue 1 (1st January 2007) - Lin, D.
Abstract : Purpose: Buffalo, WY, is a rural community, with many families owning horses and participating in rodeos. Although horse-related injuries are common, helmet use is rare. A community project was developed to identify barriers to helmet use during horseback riding and develop an effective helmet promotion campaign. Methods: Emergency room records were analyzed for the prevalence of horse-related accidents. Interviews were conducted with dude ranch owners, parents of 4H members, and riders to gain insight into possible resistance against helmet use. A literature search was conducted using PubMed to review the efficacy of helmets for equestrian use. Results: Buffalo residents' views on helmet use varied from understanding the effectiveness of helmets but placing it as a low priority to helmets being unnecessary and burdensome. Many people cited that horseback riding without the use of equestrian helmets had been done in their family for generations. A brochure was created to educate citizens on the dangers of horseback riding, the efficacy of equestrian helmets, and where to obtain them. Brochures were mailed out to all the parents with children in Buffalo's 4H horse program as well as placed in the health clinic and the boys and girls club. Johnson County Public Health agreed to hand out two free equestrian helmets and provide additional ones at a discounted rate. Conclusion: To make effective changes in attitude, additional health education will be necessary. The brochure was one step toward creating change; however, a strong, present advocate from the town would be the most effective way to sustain the campaign. Improvement can easily be measured by observing the number of helmeted riders at weekly rodeos in Buffalo.